THEME OF THE WAR IN FINE ARTS: PECULIARITY OF HISTORICAL AND CULTURAL TRANSFORMATIONS - Stoian, Svitlana (Ukrainian Cultural Studies, 2023)
The article analyzes the cultural and historical transformations of the nature of the depiction of the theme of war in fine art. It is noted that art has always responded to changes in worldview paradigms and reflected core value principles of various historical periods of human development. The emphasis of depicting the essence of the war changed from the fixation of specific events that took place in real life to the depiction of generalized metaphorical images with the participation of mythological characters that had no relation to reality and vice versa. In addition, fine art also served as a channel for the sublimation of the psychological experiences of artists who expressed their experiences related to the war through their own works. Thanks to this, powerful ingenious works of art, the relevance of which does not decrease even after several centuries, were created. The article provides a comparative analysis of the nature of the depiction of war in the art of ancient civilizations, antiquity, the Middle Ages, the Renaissance, baroque, rococo, classicism, romanticism, avant-garde art of the beginning of the 20th century, Soviet totalitarian practice as well as in modern Ukrainian art. Thanks to the research conducted, the essence and nature of the transformations, that took place in these periods, are visualized, and the direct correlation of these changes with the state and nature of culture is highlighted. Special attention is paid to the analysis of the visualization of the theme of war in the Ukrainian fine art of the totalitarian era as well as in modern art. It is noted that Ukrainian artists had creative resistance to totalitarian ideology. This was manifested in the demonstration of the tragic side of war, existential experiences, awareness of the irreversibility of death and the suffering associated with it. Attention is focused on the fact that the topic of the relationship between art and war in the context of cultural studies is rather understudied but in the context of recent occurrences in Ukraine and the world it is gaining more and more popularity, drawing attention of researchers to the analysis of these mutual influences.
Keywords: war; fine arts; culture; socio-cultural transformations; modern Ukrainian art; contemporary Ukrainian art